2014
DOI: 10.1002/iub.1273
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA expression in breast cancer varies with lymph node metastasis and other clinicopathologic features

Abstract: Breast carcinoma is the most common malignant tumor in females, and lymph node (LN) status is one of the most important prognostic factors in patients with breast cancer. MiRNAs have been shown to have important role in oncogenesis, invasion, and metastasis via epigenetic posttranscriptional gene regulation. However, lymphatic metastasis-related miRNAs of breast cancer has not been well documented. The aim of this study was to identify and evaluate miRNAs related to breast cancer LN metastasis and to explore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
44
2
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 30 publications
8
44
2
3
Order By: Relevance
“…Most of the 15 miRNAs were reported to link with breast cancer. For instance, let-7 , miR-379 , miR-381 , and miR-421 were found to be down-regulated in breast cancer25262728; miR-17 , miR-18a , and miR-9 turned out to be metastasis-associated293031; and miR-190 was detected to be related to estrogen receptor32. In addition, the functional enrichment of target mRNA showed that target mRNAs of these miRNAs were significantly ( P  < 0.01) enriched in the pathway related to cancer, such as pathways in cancer, ubiquitin-mediated proteolysis, and MAPK signaling pathway (Table S7).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the 15 miRNAs were reported to link with breast cancer. For instance, let-7 , miR-379 , miR-381 , and miR-421 were found to be down-regulated in breast cancer25262728; miR-17 , miR-18a , and miR-9 turned out to be metastasis-associated293031; and miR-190 was detected to be related to estrogen receptor32. In addition, the functional enrichment of target mRNA showed that target mRNAs of these miRNAs were significantly ( P  < 0.01) enriched in the pathway related to cancer, such as pathways in cancer, ubiquitin-mediated proteolysis, and MAPK signaling pathway (Table S7).…”
Section: Resultsmentioning
confidence: 99%
“…RT-qPCR analysis of 8 GC tissue and adjacent normal tissue samples validated that miR-564 was downregulated in GC, which was consistent with the results of miRNA microarray analysis. miR-564 has been reported to be aberrantly expressed in breast cancer (31) and chronic myeloid leukemia (32), indicating that is serves a role in cancer development. However, the molecular mechanism underlying the downregulation of miR-564 in GC remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, lymph node involvement in breast cancer is indicative of high-grade, late-stage advanced disease. In breast cancers where a lymph node could be identified using realtime RT-PCR (n=31), miR-181a was one of the eight miRNAs that was downregulated when compared to the non-lymph node (n = 42) group [32]. …”
Section: Anti-oncogenic Roles Of Mir-181amentioning
confidence: 99%